Differences in epidemiological and clinical features between adult and pediatric tracheobronchial tuberculosis patients in Southwest China - Chen, Qing; Huang, Tao; Zou, Liping; Jiang, Liangshuang; Sun, Jiying; Lu, Xiaoli; Huang, Xiaoqiu; Wu, Guihui; He, Wei (Frontiers in Public Health, 2023)
Background:Tracheobronchial tuberculosis (TBTB) is a common form of extrapulmonary tuberculosis that affects the tracheobronchial tree. However, the mechanism has not been fully elucidated. Comparisons of clinical characteristics in various age groups can aid in the understanding of TBTB. Methods:This retrospective study was conducted at the Public Health Clinical Center of Chengdu between July 2017 and December 2021, including adults and children with TBTB. Clinical data were extracted from medical records. T/T’ test, Mann-Whitney U test, Chi-square test, or Fisher’s exact test were used in this study. Results:This study enrolled 347 patients with TBTB (175 adults and 172 children). Adult females were more susceptible to TBTB, whereas gender-based differences were not observed in children. Children had a higher occurrence of irritant dry cough and fever, and acute hematogenous disseminated PTB and specific types of EPTB, but a shorter interval before diagnosis, and lower diagnostic yields compared to adults (P＜0.05). Adults presented more extensive lung lesions and cavitations as compared to children. Granulation hyperplasia and lymph fistula were more frequently observed in children, as well as airway stenosis, but less severe. Conclusions:The study revealed important variations exist in multiple respects between adults and children with TBTB.